Nový slovník cizích slov pro 21. století - Barták, Matěj; Vebrová, Jitka; Rychlá, Renata (Plot, 2008)
Slovník obsahuje přes 30 000 hesel a definic
Keywords: lingvistika, lékařská terminologie; lingvistika; Linguistics; čeština